Using of moment method for parasitic parameters of printed circuits in planar structures - Sabat, Wiesław; Kalita, Włodzimierz; Wisz, Bogusław; Sperling, Dieter (Видавництво Національного університету «Львівська політехніка», 2002)
This paper presents using of moment methodfor printed circuit residual parameters’ calculation in single-layer planar structures. In accordance to the method’s assumptions, the relations specifying the potential coefficients for printed circuit with arbitral geometric parameters were determined. Using the Mathcad program, basing on the relations as referred to above, the program was developed for calculation of unitary matrices of parasitic capacities and inductances of printed circuit of mutually parallel lines. In order to verify the developed program operation, the hybrid test printed circuits with different geometric parameters were made. The correctness of calculation procedures within the developed program was experimentally verified using the direct measurement for the capacity and the indirect measurement for the inductance.
Keywords: moment method; parasitic parameters; hybrid circuit